Compreendendo como as crianças significam o direito de brincar - Patino, Joana Fontes (2009)
This research aimed to understand how children mean the right to play. For that, assumes that the children composed a social category generational, with children experiencing their own skills, the result of the mediated relationship with the social and its transformative capacity. Adding to that, they are subject of duties with competence to means your own condition. After a long history of repression and an intense political struggle, the Doctrine of Integral Protection is inaugurated in Brazil and the Citizen (1889), which regulates the fundamental rights of all children and adolescents. Among these rights is the right to play. However, it is sufficient to provide by law, it is necessary to break with the diminishment of the play activity, still present in our society, watching it as a structuring activity of the subject and ensuring the enforcement of this right. Considering the child as the central focus of research, the research was conducted in a public school education. The subjects were six children of six years old, enrolled in 1st year of elementary school. The procedures employed for constituting the corpus of the research were: observation of children at school meetings and dialogue, monitoring of play resources such as drawings, cartoons and representative images of child rights. Also, the parents were interviewed with the goal to enlarge the understanding the context of the child. With the thematic content analysis, we raise two areas: play and children's rights. The results showed that children, however don‟t have a systematized knowledge about child rights , they understand that any elements are important for the children and your development, being the play the most recurrent, followed by education and family. The right to play configure as a necessity of the child, that even if she does not understand conceptually as a right, she feels the importance of living of the play activity